A study on automated traction control system of an electrical golf car. (31st May 2011) - Rahman, Ataur; Mohiuddin, A.K.M.; Ihsan, Sany Izan
This study presents an automated traction control system (ATCS) without incorporating the function of hydraulic system. The ATCS is used for improving the vehicle performance in terms of stability and torque or speed needed in order to produce smooth driving. Driving motor and wheel speed sensor (WSS) with RPM meter are used in this study to develop the sufficient torque or speed on demand of the driving wheel. The current flow is controlled to the driving motor with the help of electronic proportional valve. A slope sensor is used in the proposed system to enhance the power supply to the driving motor when the vehicle will be in the grade of 10%-20%. SolidWorks simulation and laboratory experiment has been performed to investigate the performance of the designed and developed automated traction control system on the dry and slippery surface.